Laparoscopic liver resection： Experience based guidelines - Coelho, Fabricio Ferreira (World journal of gastrointestinal surgery, 2016)
Laparoscopic liver resection （LLR） has been progressivelydeveloped along the past two decades. Despiteinitial skepticism, improved operative results madelaparoscopic approach incorporated to surgical practiceand operations increased in frequency and complexity.Evidence supporting LLR comes from case-series,comparative studies and meta-analysis. Despite lack oflevel 1 evidence, the body of literature is stronger andexisting data confirms the safety, feasibility and benefitsof laparoscopic approach when compared to openresection. Indications for LLR do not differ from thosefor open surgery. They include benign and malignant（both primary and metastatic） tumors and living donorliver harvesting. Currently, resection of lesions locatedon anterolateral segments and left lateral sectionectomyare performed systematically by laparoscopy in hepatobiliaryspecialized centers. Resection of lesions locatedon posterosuperior segments （1, 4a, 7, 8） and majorliver resections were shown to be feasible but remaintechnically demanding procedures, which should bereserved to experienced surgeons. Hand-assisted andlaparoscopy-assisted procedures appeared to increasethe indications of minimally invasive liver surgery andare useful strategies applied to difficult and majorresections. LLR proved to be safe for malignant lesionsand offers some short-term advantages over openresection. Oncological results including resection marginstatus and long-term survival were not inferior to openresection. At present, surgical community expects highquality studies to base the already perceived betteroutcomes achieved by laparoscopy in major centers＇practice. Continuous surgical training, as well as newtechnologies should augment the application of lap-aroscopic liver surgery. Future applicability of newtechnologies such as robot assistance and image-guidedsurgery is still under investigation.